Strategic advertising management - Percy, Larry (Oxford University Press, 2009)
"Strategic Advertising Management presents a strong theoretical foundation for the development of effective marketing communication. The text then outlines how this theory can be used by managers in the development of effective marketing communication plans and creative executions. The book treats the subject as an integrated whole, looking at how the various aspects of advertising fit together." "In this latest edition the topic of promotion has been woven throughout the text. A new chapter on message delivery has been introduced, looking at basic types of promotion as well as alternative ways of delivering advertising and promotion type messages, such as sponsorships and event marketing. A new chapter on understanding cultural differences has also been included for the new edition, giving consideration to issues of culture in respect of advertising strategy and execution. Case studies have been introduced to allow students to critically reflect on the material being covered in each chapter."--BOOK JACKET